Unenthusiastic Europeans or affected English - Komar, Smiljana (ELOPE (Ljubljana), 2005)
Attitudes and emotions are expressed by linguistic as well as extra-linguisticfeatures. The linguistic features comprise the lexis, the word-order and the intonation of the utterance. The purpose of this article isto examine the impact of intonation on our perception of speech. I will attempt to show that our expression, as well as our perception and understanding of attitudes and emotions are realized in accordance with the intonation patterns typical of the mother tongue. When listening to non-nativespeakers using our mother tongue we expect and tolerate errors in pronunciation, grammar and lexis but are quite ignorant and intolerant of non-native intonation patterns. Foreigners often sound unenthusiastic to native English ears. On the basis of the results obtained from an analysis of speech produced by 21 non-native speakers of English, including Slovenes, I will show that the reasons for such an impression of being unenthusiastic stemfrom different tonality and tonicity rules, as well as from the lack of the fall-rise tone and a very narrow pitch range with no or very few pitch jumps or slumps.
Keywords: angleščina; govor; kontrastivna lingvistika; tonematika